Increasing Student Learning Activities Through the Implementation of Interactive E-Modules in Science Tutorial Models on Elementary School Ecosystem Materials - Zulfi Idayanti*; Muh Asharif Suleman; Maemonah Maemonah (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
The development of teaching materials requires educators to innovate in creating effective learning. E-module is one of the technology-based teaching materials developed to encourage students' natural science learning activities independently. This study aims to analyze the use of e-modules in increasing students' independent learning activities, especially in science subjects. This research is a quantitative type with 21 students in class V-A Madrasah Ibtidaiyah as the subject of the research. The data collection method is in the form of a learning activity questionnaire. The results showed that the use of e-module teaching materials can increase student learning activities by 44.74% with the most activity criteria being moderate (3-5 activities). This is because the density of extracurricular activities that must be followed at school makes children lack independent learning activities outside the school environment. With this teaching material, it is hoped that it will be able to support students' independent learning activities outside the school environment comfortably and increase students' enthusiasm for learning